AIW1 and AIW2, two ABA-induced WD40 repeat-containing transcription repressors function redundantly to regulate ABA and salt responses in Arabidopsis. Issue 1 (1st January 2020) - Wang, Xutong; Wang, Wei; Wang, Yating; Zhou, Ganghua; Liu, Shanda; Li, Dongqiu; Adnan,; Hussain, Saddam; Ahmed, Sajjad; Zhang, Chen; Yan, Li; Wang, Tianya; et al.
ABSTRACT: WDR proteins in plants regulate multiple aspects of plant growth and development, as well as plant responses to environmental stimuli. Here, we report the identification of AIW1 (ABA-induced WD40-repeat 1) and AIW2 as novel regulators of salt responses in Arabidopsis. RT-PCR results show that the expression of AIW1 and AIW2 were induced by ABA. Transfection assays in protoplasts show that AIW1 and AIW2 were nucleus proteins and functioned as transcription repressors. When overexpressed in Arabidopsis, AIW1 promoted root elongation, and reduced seedlings sensitivity to ABA. On the other hand, aiw1 aiw2 double mutants showed an increased sensitivity to ABA in seed germination assays. In addition, salt tolerance was reduced in the 35S:AIW1 transgenic plants in root elongation assays. Taken together, our results suggest that AIW1 and AIW2 are ABA-induced plant specific WD40 repeat-containing transcription repressors, and AIW1 and AIW2 function redundantly to regulate ABA and salt responses in Arabidopsis.